Legitimating identities : the self-presentation of rulers and subjects - Barker, Rodney S. (Cambridge University Press, 2001)
All rulers spend time convincing themselves of their right to rule. Legitimating Identities draws on a growing body of research in political science, history, and sociology to show how governments of all kinds devote resources and energy to cultivating their identity for their own self-justification and esteem.